2003
DOI: 10.1038/sj.hdy.6800241
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of two distinct reproductive strategies in sexual and asexual field populations of an endoparasitic wasp, Venturia canescens

Abstract: Asexual (thelytokous) females of the parasitoid Venturia canescens, which develop inside another insect, exhibit evolutionarily stable mixtures of life-history strategies, allowing two genetically distinct wasp lines to coexist sympatrically on the same host resources. Since the two asexual lines differ in a virus-like particle protein-coding gene (VLP1), the question is whether the VLP1 gene is genetically associated with the phenotype. The recent isolation of facultative sexual (arrhenotokous) and asexual V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Previous knowledge on the life history of the thelytokous and arrhenotokous V. canescens is also consistent with this hypothesis. For instance, the larger egg complement and number of ovarioles in thelytokous females than in arrhenotokous females (Li et al 2003; suggest that thelytokous females would benefit to a greater extent from high host availabilities, such as those in granaries and mills (Papaj 2000). Other differences in patch exploitation behaviour between arrhenotokous and thelytokous females were found by Thiel et al (in press).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous knowledge on the life history of the thelytokous and arrhenotokous V. canescens is also consistent with this hypothesis. For instance, the larger egg complement and number of ovarioles in thelytokous females than in arrhenotokous females (Li et al 2003; suggest that thelytokous females would benefit to a greater extent from high host availabilities, such as those in granaries and mills (Papaj 2000). Other differences in patch exploitation behaviour between arrhenotokous and thelytokous females were found by Thiel et al (in press).…”
Section: Discussionmentioning
confidence: 82%
“…The sampling procedure does not allow one to estimate the original number of females that attacked the hosts in the pieces of cardboard, but the number of sampling points and their distance apart ensure an adequate number of foundress females. As Beck et al (1999Beck et al ( , 2001 and Li et al (2003) suggested that a deletion in the sequence encoding a virus-like particle protein has pleiotropic effects on the reproductive biology of V. canescens, only wasps carrying the wild-type allele (called RP by Hellers et al 1996) were used. However, it has subsequently been shown that the strain used in this experiment displays no such pleiotropic effects on reproductive biology (Amat et al 2003).…”
Section: Biological Details and Culturesmentioning
confidence: 99%
“…Schneider et al (2003) detected gene flow between arrhenotokous and thelytokous populations in the laboratory. It could be shown that there is a genetic basis for the thelytoky in V. canescens (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, investigations of natural populations from several locations have revealed that wasps displaying similar clusters of phenotypic traits to both laboratory lines occur in the field and can be collected from the same locations (Li et al, 2003;Amat et al, 2003).…”
Section: The Modelmentioning
confidence: 98%
“…France, using the VLP1 gene as a marker, found that wasps displaying phenotypic clusters qualitatively similar to the laboratory RM-and RP-lines co-occur in natural populations (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%